2014
DOI: 10.1080/10911359.2014.923359
|View full text |Cite
|
Sign up to set email alerts
|

Food-Related Behaviors of Women in Substance Abuse Recovery: A Photo-Elicitation Study

Abstract: The aim of this multi-method qualitative study was to explore the eating behaviors and food choices of nine purposively sampled low-income women aged 29 to 40 years who were engaged in a residential substance use disorders recovery program. Findings were limited to photo-elicitation interviews with the women that focused on nutritional choices and issues outside their family context. Consensual data analysis revealed a recovery process that began with cognitive reawakening and an increased focus on and desire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Participants were then asked to take photographs related to study research questions and what was discussed in the FGD-style workshop. The use of photographs in conjunction with more traditional qualitative methods like FGDs [also known as 'Photo Elicitation' (Harper, 2002)] has shown in a wide variety of studies to be effective in gathering information and views from participants regarding their lives in relation to a specific research topic-views which may have otherwise not been as easily communicated when using qualitative methods alone (Snyder and Kane, 1990;Clark-Ibáñez, 2004;Mondelco, 2013;Ali-Khan and Siryb, 2014;Wall-Bassett et al, 2014). It has also been demonstrated that this approach encourages more direct involvement by study participants in the research process, particularly in the gathering and interpreting of relevant data (Bignante, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were then asked to take photographs related to study research questions and what was discussed in the FGD-style workshop. The use of photographs in conjunction with more traditional qualitative methods like FGDs [also known as 'Photo Elicitation' (Harper, 2002)] has shown in a wide variety of studies to be effective in gathering information and views from participants regarding their lives in relation to a specific research topic-views which may have otherwise not been as easily communicated when using qualitative methods alone (Snyder and Kane, 1990;Clark-Ibáñez, 2004;Mondelco, 2013;Ali-Khan and Siryb, 2014;Wall-Bassett et al, 2014). It has also been demonstrated that this approach encourages more direct involvement by study participants in the research process, particularly in the gathering and interpreting of relevant data (Bignante, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…For some of the women, the recovery process resulted in the reemergence of a previously held desire for healthy food choices that had been suppressed or ignored during active substance use. They centered the reawakening of their health-related concerns in recovery primarily on their children and, for some women, a personal desire to reduce their body weight or improve a pre-existing disorder such as hypertension or high serum cholesterol (Wall-Bassett et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this study was to investigate the influences on food choices made by mothers living with their children in a residential substance use disorder recovery program. The women’s intrapersonal nutritional choices and issues excluding family context have been reported elsewhere (Wall-Bassett et al, 2014). This report addresses the family context of participants’ food choice decisions while living in a residential treatment facility where they were responsible for procuring and preparing food for themselves and the children who lived with them.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…To some extent, recovery from drug abuse is actually a process centred on stimulating and maintaining the motivation for change [ 23 ]. Positive behavioural changes are likely to occur only when a drug abuser reawakens cognitively [ 24 ]. Previous studies on the motivation for drug detoxification mainly focus on the investigation of motivation status and the analysis of influencing factors.…”
Section: Literature Reviewmentioning
confidence: 99%